Selected Topics of High Speed Machining Analysis - Initial lecture for VIII International Conference HIGH SPEED MACHINING - ŁODYGOWSKI, Tomasz; RUSINEK, Alexis; JANKOWIAK, Tomasz; SUMELKA, Wojciech (Engineering Transactions, 2012)
Some aspects of numerical analysis of problems related to high strain rates with thermal effects are considered. The attention is focused on constitutive modelling that describes the ac- companied phenomena like plastic strain localization and softening. The importance of proper formulation of failure criteria is stressed. Also the complexity of computations is discussed.